The effect of body composition on strength and power in male and female students - Ghassen Ben Mansour (BMC, 2021)
Abstract Purpose The aim of this study is to determine and to compare the effect of sex differences in percentage of body fat on the strength and power performances of the legs and arms during short maximal exercise. Methods 72 male and 64 female students aged 20 to 23 years were enrolled in this study. After assessing their morphological characteristics (body mass, height and percentage of fat mass), a squat jump test (SJ), a 5 successive jump test (5JT), a hand gripping (HG) and back strength (BS) tests have been conducted for each subject. Male students were re-tested after being weighed down with a weight equivalent to the mean differences in body fat recorded between the two sexes in the form of a loaded worn vest. Results Male are 15.7% heavier and 7.4% taller and presented a percentage of fat mass (17.2 ± 1.8%) significantly (p < 0.001) lower than that of women subject (25.0 ± 2.5%) (difference male vs female for fat mass: -45.5%). HG, BS, 5JT and SJ performances were significantly higher in males (44 ± 5 kg, 141 ± 2 kg, 11 ± 1 m and 32.4 ± 2,7 cm, respectively) than in females (31.0 ± 4 kg, 81.6 ± 13 kg, 8.7 ± 0.7 m and 21.1 ± 1.9 cm, respectively). In the control (unloaded) condition, the relative difference between males and females represented 23.5% and 34.7% of the male performances for 5JT and SJ, respectively. In the weighted condition, the relative difference between weighted males and females still represented 11.7% and 23.8% of the weighted male performances for 5JT and SJ, respectively. Cancelling the sex difference in fat mass by adding weight in males reduced by 50.1% the sex difference during 5JT and 31.4% and 71.7% for hight and power results, respectively during SJ test. Conclusion During short and maximal exercise, male performed better with their hands, back and legs than female students. Excess fat for female students has a disadvantageous effect on vertical and horizontal jumps performances. The persistence of sex differences after weighting of male students indicates that body fat is responsible for 30 to 70% of the observed differences between sexes performances and power outcomes during jump tests.